Perampanel and childhood absence epilepsy: A real life experience - Operto, Francesca Felicia; Orsini, Alessandro; Sica, Gianpiero; Scuoppo, Chiara; Padovano, Chiara; Vivenzio, Valentina; de Simone, Valeria; Rinaldi, Rosetta; Belfiore, Gilda; Mazza, Roberta; Aiello, Salvatore; Vetri, Luigi; et al. (Frontiers in Neurology, 2022)
Objectives The aim of our study was to evaluate the effectiveness and tolerability of perampanel (PER) as first add-on and as second line monotherapy in subjects with childhood absence epilepsy. Methods Our sample consisted of 20 patients with childhood absence epilepsy, aged between 8 and 10, already in therapy with a first antiseizure medication with incomplete seizure control. PER was added as first add-on in a dose ranging from 3 to 8 mg/die with 1- 2 mg/week increments. The patients that were seizure-free were shifted to a PER monotherapy. All patients underwent a standardized neuropsychological evaluation in order to assess non-verbal intelligence and executive functions before adding PER and after 6 months of drug therapy. All parents completed two questionnaires, in order to assess the emotional-behavioral problems and parental stress. Results 15/20 patients responded to add-on PER and were seizure-free, in 3/20 patients we observed a reduction of seizure frequency <50%, and in the 2 remaining patients the add-on therapy with PER did not lead to a reduction in seizures frequency from baseline. The patients who were seizure-free were switched to PER monotherapy. 9/15 patients remained seizure-free in monotherapy with PER. In the first month of therapy with PER 2/20 patients (10%) reported mild, transient side effects of irritability, headache and dizziness, which did not lead to discontinuation of therapy. Adjunctive treatment with PER did not negatively affect non-verbal intelligence, executive functions, emotional/behavioral symptoms of children and parental stress levels. Significance Our clinical experience in real life showed that PER appears to be effective in the control of absence seizures in childhood absence epilepsy, with a favorable tolerability profile. PER would seem effective on absence seizures even in monotherapy. Further studies with larger samples, longer follow-up and controlled vs. placebo (or other first choice antiseizure medications) are needed to confirm our data.